Synthesis of (Z)-3-[amino(phenyl)methylidene]-1,3-dihydro-2H-indol-2-ones using an Eschenmoser coupling reaction - Marek, Lukáš; Kolman, Lukáš; Váňa, Jiří; Svoboda, Jan; Hanusek, Jiří (Beilstein-Institut, 2021)
A highly modular method for the synthesis of (Z)-3-[amino(phenyl/methyl)methylidene]-1,3-dihydro-2H-indol-2-ones starting from easily available 3-bromooxindoles or (2-oxoindolin-3-yl)triflate and thioacetamides or thiobenzamides is described. A series of 49 compounds, several of which have previously been shown to possess significant tyrosin kinase inhibiting activity, was prepared in yields varying mostly from 70 to 97% and always surpassing those obtained by other published methods. The method includes an Eschenmoser coupling reaction, which is very feasible (even without using a thiophile except tertiary amides) and scalable. The (Z)-configuration of all products was confirmed by NMR techniques.
Syntéza (Z)-3-[amino(fenyl)methyliden]-1,3-dihydro-2H-indol-2-onů s využitím Eschenmoserovy reakce
Keywords: 3-bromooxindoles; Eschenmoser coupling reaction; thioamides; thiobenzamides; (Z)-3-[amino(phenyl)methylidene]-1,3-dihydro-2H-indol-2-ones; 3-bromoxindoly; Eschenmoserova reakce; thioamidy; thiobenzamidy; (Z)-3-[amino(fenyl)methyliden]-1,3-dihydro-2H-indol-2-ony